The environmental impact of religious beliefs in the East and West: evidence from China - Yang, Junyan; Lu, Chuntian (Frontiers in Psychology, 2024)
This study explores the influence of religious beliefs on environmental attitudes and behaviors in China. Using data from the 2021 Chinese General Social Survey (CGSS), two structural equation models were constructed to examine the mediating roles of natural empathy and anthropocentrism in the relationship between environmental awareness and willingness to make sacrifices for environmental protection. The results indicated that while environmental awareness positively influenced willingness to sacrifice, natural empathy did not significantly mediate this relationship. Conversely, anthropocentrism negatively mediated the relationship, suggesting that individuals with anthropocentric tendencies were less willing to make personal sacrifices for environmental protection. Furthermore, a multi-group analysis revealed that individuals with traditional Eastern religious beliefs (Buddhism, Taoism, and folklore) exhibited higher environmental awareness and willingness to sacrifice compared to those with no religion or traditional Western (Christianity) religious beliefs. These findings highlight the influence of religious traditions, particularly the emphasis on nature reverence in Eastern religions, on shaping pro-environmental attitudes and behaviors. The study contributes to understanding the complex interplay between religious beliefs, environmental values, and sustainable behaviors in the Chinese context.